l-arginine modulates inflammation and muscle regulatory genes after a single session of resistance exercise in rats - Morais, S. R.L. [UNESP]; Brito, V. G.B. [UNESP]; Mello, W. G. [UNESP]; Oliveira, S. H.P. [UNESP] (Wiley, 2018)
We investigated the skeletal muscle adaptation to l-arginine supplementation prior to a single session of resistance exercise (RE) during the early phase of muscle repair. Wistar rats were randomly assigned into non-exercised (Control), RE plus vehicle (RE); RE plus l-arginine (RE+L-arg) and RE plus aminoguanidine (RE+AG) groups. Animals received four doses of either vehicle (0.9% NaCl), l-arg (1 g/b.w.), or AG (iNOS inhibitor) (50 mg/b.w.). The animals performed a single RE session until the concentric failure (ladder climbing; 80% overload) and the skeletal muscles were harvested at 0, 8, 24, and 48 hours post-RE. The RE resulted in increased neutrophil infiltrate (24 hours post-RE) (3621 vs 11852; P<.0001) associated with enhanced TNF-α (819.49 vs 357.02; P<.005) and IL-6 (3.84 vs 1.08; P<.0001). Prior, l-arginine supplementation attenuates neutrophil infiltration (5622; P<.0001), and also TNF-α (506.01; P<.05) and IL-6 (2.51, P<.05) levels. AG pretreatment mediated an inhibition of iNOS levels similar to levels found in RE group. RE animals displayed increased of atrogin-1 (1.9 fold) and MuRF-1 (3.2 fold) mRNA levels, reversed by l-arg supplementation [atrogin-1 (0.6 fold; P<.001); MuRF-1 (0.8-fold; P<.001)] at 24 hours post-RE. MyoD up-regulated levels were restricted to l-arg treated animals at 24 hours (2.8 vs 1.5 fold; P<.005) and 48 hours post-RE (2.4 vs 1.1 fold; P<.001). AG pretreatment reversed these processes at 24 hours [atrogin-1 (2.1 fold; P<.0001); MuRF-1 (2.5 fold; P<.0001); MyoD (1.4 fold)]. l-arginine supplementation seems to attenuate the resolution of RE-induced muscle inflammation and up-regulates MyoD expression during the early phase of muscle repair.
Keywords: atrogin-1; IL-6; iNOS; l-arginine; MuRF-1; MyoD; resistance exercise; skeletal muscle repair